Spinal Anesthesia is Superior to General Anesthesia for Percutaneous Achilles Tenotomy in Infants. Issue 6 (12th July 2021) - Acquaviva, Michael A.; Caltoum, Christine B.; Bielski, Robert J.; Loder, Randall T.; Boyer, Tanna J.; Cossu, Anne E.; Castelluccio, Peter F.
Abstract : Background: Concern about the effects of inhaled, halogenated anesthetics on neurodevelopment of infants has renewed interest in regional anesthesia as an alternative to general anesthesia (GA). Infants undergoing percutaneous Achilles tenotomy (PAT) are well suited for spinal anesthesia (SP). Methods: Thirty infants (mean age: 2.3 mo) undergoing PAT with SP were compared with 15 infants (mean age: 2.0 mo) undergoing PAT with GA. Data collected included perioperative times, heart rate and blood pressure, and the administration of opioids. Results: Ten of 15 GA (67%) patients received perioperative opioids as opposed to 1 of 30 SP patients (3.3%) ( P <0.0001). The time from the start of anesthesia to the start of surgery was shorter in the SP group (8.5 vs. 14 min, P <0.0009). The time from the start of anesthesia to first oral intake was shorter in the SP group (12 vs. 31 min, P <0.0033). The time of first phase recovery (phase 1 post anesthesia care unit) was shorter in the SP group (15.5 vs. 34 min, P <0.0026). Surgery time was not significantly different between the groups (SP: 15.5 min, GA: 15 min, P =0.81). Conclusion: Infants undergoing PAT with SP received less opioid, did not require an airway device, did not receive potent inhaled, halogenated hydrocarbon anesthetics, and exhibited faster and qualitatively better postoperative recovery. Level of Evidence: Level III—case control study.